Towards a Comprehensive School Effectiveness Model of Citizenship Education: An Empirical Analysis of Secondary Schools in The Netherlands - Manja Coopmans; Geert Ten Dam; Anne Bert Dijkstra; Ineke Van der Veen (Social Sciences, 2020)
We still have only a limited understanding of the effectiveness of schools in promoting citizenship, the factors explaining this effectiveness and the way in which these aspects interact. Using elaborate cross-sectional data from students, teachers, team leaders and school leaders at 78 Dutch secondary schools, this study empirically examines a school effectiveness model of citizenship education in order to achieve a more comprehensive explanation of citizenship competence acquisition. Using multilevel structural equation models, we analyze direct and indirect school-level predictors of student knowledge, attitudes and self-evaluated skills regarding citizenship. Four aspects of citizenship education are examined: the school’s policies regarding citizenship education, its teaching practices, and its professional and pedagogical learning environment (i.e., teaching community and classroom climate). With respect to school policies, positive effects are found for the attention paid to citizenship education in staff meetings. The professional learning environment is related to students’ citizenship competences mainly indirectly, via the average classroom climate. Effects of teaching practices vary: more emphasis on monitoring is more frequently found at schools with lower average levels of citizenship competences, whereas schools that let students choose their own topics in class have on average higher levels of citizenship competences.